A Case of Fabry Disease With Lacrimal Gland Involvement. Issue 2 (18th January 2023) - Bruce, Carleigh N.; Mancera, Norberto; Grover, Abhinav; Esmaili, Neda
Abstract : Fabry disease is an X-linked lysosomal storage disease resulting from an error in the glycosphingolipid metabolic pathway, which leads to accumulation of globotriaosylceramide in lysosomes of the skin, kidneys, heart, brain, and other organs. There are no existing reports of histologically proven lacrimal gland involvement in Fabry disease. The authors report the case of a 26-year-old male with Fabry disease who presented with bilateral upper eyelid dermatochalasis, steatoblepharon, and prolapsed lacrimal glands. The patient underwent surgical repair of the upper eyelids and biopsy of the lacrimal glands. The pathologic assessment demonstrated lamellated intracytoplasmic inclusions characteristic of Fabry disease. The prevalence of globotriaosylceramide lacrimal gland deposition in Fabry disease and the effect on lacrimal gland morphology and function have yet to be determined. Abstract : A case of biopsy proven lacrimal gland involvement in Fabry disease is presented. This finding adds to the understanding of glycosphingolipid deposition. Additional research on the effect on lacrimal gland function and morphology is needed.